Determination of Gravity Acceleration with Smartphone Ambient Light Sensor - Silva-Ale, J (American Institute of Physics, 2021)
Among the serious experimental uses given to smartphones in physics, the use of integrated sensors, video analysis, and mixed uses as simultaneous material and instruments stand out for their frequency. Regarding the use of integrated sensors, there are many proposals that use the accelerometer, the magnetometer, or other sensors (e.g, camera or microphone) to find experimental values of physical constants, such as acceleration of gravity (g), thereby trying to contribute to the studies of statics, kinematics, and dynamics. However, there are few studies that use the ambient light sensor for this kind of purpose. © 2021 American Association of Physics Teachers.